Subcutaneous immunotherapy induces alterations in monocytes and dendritic cells homeostasis in allergic rhinitis patients - Sousa, Letícia (2018)
Background: Specific subcutaneous immunotherapy (SCIT) can achieve long-term remission in patients with allergic rhinitis (AR) through complex and still unknown mechanisms. The aim of this study is to evaluate the effect of SCIT over CD16+ and CD16− monocytes, myeloid (mDCs) and plasmacytoid dendritic cells (pDCs) in patients with AR, comparatively to pharmacological standard treatment (non-SIT). Methods: The relative frequency and absolute number of monocytes and DC subsets, the frequency of these cells producing TNFα after in vitro stimulation with Dermatophagoides pteronyssinus (Dpt) extract, and the expression levels of receptor-bound IgE or IgG were assessed by flow cytometry, in peripheral blood samples from 23 healthy individuals (HG) and 43 participants with AR mono-sensitized to Dpt; 10 with non-SIT treatment and 33 under SCIT, just before (SCIT-T0) and 4 h after administration (SCIT-T4). Moreover, IFNα mRNA expression was evaluated in purified pDCs, by qRT-PCR. Results: After SCIT administration we observed a strong decrease of circulating pDCs, although accompanied by higher levels of IFNα mRNA expression, and an increase of circulating CD16+ monocytes. AR participants under SCIT exhibited a higher expression of receptor-bound IgE in all cell populations that expressed the high affinity receptor for IgE (FcεRI) and a higher frequency of CD16+ monocytes producing TNFα. Conversely, we observed a decrease in the frequency of mDCs producing TNFα in AR under SCIT, similar to the observed in the control group. Conclusions: SCIT seems to induce numeric, phenotypic, and functional changes in circulating monocytes and dendritic cells, contributing at least in part to the well described immunological alterations induced by this type of immunotherapy.